1984
DOI: 10.1063/1.446969
|View full text |Cite|
|
Sign up to set email alerts
|

A comparative theoretical analysis of the photochemistry of the methyl radical and related systems

Abstract: Portions of the ground and 3s,3px,y,z Rydberg excited state C–H and C–H2 fragmentation pathways are computed for the CH3 radical at the 4-31G+Rydberg+CI level. It is concluded that the B̃ state photochemistry of CH3 should give principally C–H bond rupture in analogy with the N–H bond rupture occurring in the à state of NH3. Higher energy photolyses should give a mixture of products whose mechanisms of formation will be difficult to establish. Rydberg extended molecular orbital and state correlation diagrams … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(9 citation statements)
references
References 60 publications
1
7
1
Order By: Relevance
“…The spectra show sharp peaks corresponding to transitions from 3s to 3p z , 3p xy , as well as higher-lying Rydberg states of the methyl radicals. We note here that the 5 3p xy Rydberg state in methyl radicals, while predicted computationally, 25,26 appears not to have been previously observed experimentally. REMPI 27,28,29,30 as well as other techniques 31,32 have been applied to detection of methyl radicals.…”
Section: Introductioncontrasting
confidence: 48%
“…The spectra show sharp peaks corresponding to transitions from 3s to 3p z , 3p xy , as well as higher-lying Rydberg states of the methyl radicals. We note here that the 5 3p xy Rydberg state in methyl radicals, while predicted computationally, 25,26 appears not to have been previously observed experimentally. REMPI 27,28,29,30 as well as other techniques 31,32 have been applied to detection of methyl radicals.…”
Section: Introductioncontrasting
confidence: 48%
“…Analysis of the tunneling rates using a cubic potential barrier places the barrier at 1.38 Å along the C−H dissociation coordinate with a height of 2200 cm -1 . , The 4-31G+ Rydberg+CI ab initio calculation by Yu et al examined the C−H and C−H 2 dissociation pathways for the methyl radical B̃ state. This calculation was qualitatively correct but did not quantitatively capture the shape of the photoactive B̃ state PES, overestimating the barrier height and position along the C−H coordinate.…”
Section: Ch3 B Bandmentioning
confidence: 99%
“…Theoretical studies on the predissociation dynamics of the methyl radical are very scarce. 16,20,21 In the work of Yu et al, 20 a small basis set RHF calculation was performed to obtain semiquantitative information about the relative barrier heights of radical (CH 3 -CH 2 + H) and molecular (CH 3 -CH + H 2 ) predissociation pathways from the ground, 3s and 3p states of the methyl radical. The group also used calculated relative energies of products and concluded that at the excitation energy of the 3p z state, it is thermodynamically possible to form the X ˜3B 1 , 1 1 A 1 , 1 1 B 1 and 2 1 A 1 states of CH 2 as the product of radical predissociation, and CH(A 2 D) and CH(X) as products of molecular predissociation.…”
Section: Introductionmentioning
confidence: 99%